If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 12) = 48 Reorder the terms: 3(12 + 4x) = 48 (12 * 3 + 4x * 3) = 48 (36 + 12x) = 48 Solving 36 + 12x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 12x = 48 + -36 Combine like terms: 36 + -36 = 0 0 + 12x = 48 + -36 12x = 48 + -36 Combine like terms: 48 + -36 = 12 12x = 12 Divide each side by '12'. x = 1 Simplifying x = 1
| 45+35c=b | | 1-5a+a-8= | | 1607-1531= | | 118=-16x^2+80x | | 5q-6=2(q+3) | | v+4v= | | -1(x-4)+2=6(x+3) | | 4x+11x=-2 | | 6+3x=-15-4x | | m-4-6m= | | 3(3k+6)-8= | | 2x-9+5+6x= | | 10y=3x | | 9x-9=8x-13 | | -8k-10k= | | 4x+3+5= | | 4x+7=-8x+7 | | 8v^3+18v^2-56v= | | 1.1y+1.4=8 | | 5x+7=7-2x | | 7(x-2)=3+7x | | -12-5n+n=n-2 | | 14-n-7=5n+1 | | 1-7k=1+3k+4k | | 8-9x+10x=5 | | 8b+6=-9+3b | | 32-6b-5b=7.25 | | 3+3x=x-3 | | 1+7r=-7+3r | | 2(5x-1)=3x(x+1) | | 8x-2=-7+7x | | 2x+8=-5 |